“Kanala, tamaaf, tramkassie, en stuur krieslam”; Lexical and phonological echoes of Malay in Cape Town - Hoogervorst, Tom (Wacana, Journal of the Humanities of Indonesia, 2021)
This article traces a largely forgotten Malay dialect which was historically in use among South African Muslims of Southeast Asian origin. Its use reached its pinnacle in the eighteenth and nineteenth century. Some elements of the Cape Malay grammar, especially its phonology, can be reconstructed through early- and mid-twentieth-century documents, most of which were written by outsiders when it was no longer passed on as a first language. When read linguistically, these sources reveal that the Malay of Cape Town resembled that of Batavia, Eastern Indonesia, and Sri Lanka. In a later developmental stage, Cape Malay adopted linguistic features from other languages spoken in the Western Cape. Yet influence took place in multiple directions and several non-standard varieties of Afrikaans exhibit lexical influence from Malay. As such, Cape Malay language history is relevant to those interested in Southeast Asia as well as South Africa.